2019
DOI: 10.1016/j.red.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The use of collateral in bilateral repurchase and securities lending agreements

Abstract: We use unique data from U.S. bank holding company-affiliated securities dealers to study the use of collateral in bilateral repurchase and securities lending agreements. Market participants' use of collateral differs substantially across asset classes: for U.S. Treasury securities transactions, we find that haircuts are large enough to provide full protection from default, whereas the same is not usually true for equities transactions. Further, although most of the equities in our sample are each associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 41 publications
1
24
1
Order By: Relevance
“…6 Moreover, data on loan terms for securities used as collateral are only now beginning to be collected in the United States on a limited basis. See, for instance, Baklanova et al (2017). experimental data.…”
mentioning
confidence: 99%
“…6 Moreover, data on loan terms for securities used as collateral are only now beginning to be collected in the United States on a limited basis. See, for instance, Baklanova et al (2017). experimental data.…”
mentioning
confidence: 99%
“…Data on the loan terms for U.S. securities used as collateral in domestic funding markets are only beginning to be collected and used in limited samples (see Copeland, Martin and Walker (2014) and Baklanova et al (2017) for evidence). In the absence of direct evidence to justify our conjecture, one could instead consider proxies for cross-country differences in demand for and supply of collateral.…”
Section: Discussionmentioning
confidence: 99%
“…Auh and Landoni (forthcoming) use micro data from an asset manager to show that clients may face a choice of different haircut-financing rate pairs for particular collateral at any point in time. Baklanova, Caglio, Cipriani, and Copeland (2017) use data provided from several banks to document the patterns of terms across asset classes, but many of their results focus on the Treasury market. A 2010 study published by the Committee on the Global Financial System (CGFS, 2010) reported the results of interviews with several funding-market participants.…”
Section: Review Of Securities Financingmentioning
confidence: 99%
“…In particular, they include securities borrowing and transactions with other dealers. Evidence in Gorton and Metrick (2012b) and Baklanova et al (2017) suggests that these two categories in fact constitute the majority of dealer activity. 13 Even so, the data do not suggest that financing volumes are very sensitive to changes in terms (or vice versa).…”
Section: Stylized Facts About Securities Financing Termsmentioning
confidence: 99%
See 1 more Smart Citation